Apartment layout and privacy satisfaction - Wahid, Julaihi; Khozaei, Fatemeh (2008)
Housing design has always been a crucial subject of architect’s concern. Architecture in general and housing design in particular has often been criticized by some architects and also in academic literature for not fulfilling people's needs and requirements. The alleged failure of modern housing over the last fifty years has often been attributed and related to a perceived break in the continuity of tradition in the design and layout of the new dwellings as provided by developers. In particular the housing types introduced by the western architecture are not conformed to the traditional nor to the apparently desired new ways of life of the majority of Muslims families in Iran. It has been admitted that the physical layout of the traditional houses is in consonance with the cultural norms and fulfilled the level of privacy in residential design, contrarily, in the middle of the twentieth century there was a break in cultural continuity with the introduction of new housing typology. These housing types were responded to a new set of needs but privacy needs in particular disappear in these transitions. The aim of this article is to investigate the apartment layout in the contemporary apartments of Tehran from privacy perspectives. In this paper the authors also attempt to focus on the potentials of achieving privacy according to the Muslim perspectives. To achieve this goal, the information was gathered from 200 questionnaires on how the occupants react towards the element of privacy in different apartment layouts. The results were used to provide a guideline for apartment layouts design in order to achieve the highest level of privacy. Finally the findings were used for analyzing the level of privacy in the housing plan. This study believes that this approach can be applied for analyzing different layouts of residential environments regardless of cultural background.